Sex-specific differences in adrenocortical attunement in mothers with a history of childhood abuse and their 5-month-old boys and girls - Fuchs, Anna; Möhler, Eva; Resch, Franz; Kaess, Michael (Journal of neural transmission, 2016)
Recent evidence points to the existence of a neurobiological attunement between mother and child, e.g., associations between maternal and child hypothalamic-pituitary-adrenal (HPA) axis functioning. As maternal history of abuse (HoA) has been shown to negatively affect mother-child interaction and HPA-axis functioning, we theorized those experiences to exert an influence on cortisol attunement, and we examined the role of infant gender in this context. Shortly after birth of their first child, a community sample of women was screened using the Childhood Trauma Questionnaire. Mothers reporting moderate or severe sexual and/or physical abuse were included in the maltreatment group (n = 41; MG) and compared with a non-maltreated comparison group (n = 47; CG). At the child’s age of 5 months, mother and infant baseline salivary cortisol was collected on two consecutive days between 11 and 1 o’clock. Correlation analyses confirmed an association between maternal and infant salivary cortisol levels for the complete sample. However, hierarchical regression models revealed a moderating role of maternal HoA and infant gender: in the CG, cortisol attunement was only significant in mother-daughter dyads, whereas in the MG, we found cortisol levels to be associated only in mother-son dyads. Consequently, alterations of neurobiological attunement between mother and child might compose a mechanism for the transgenerational transmission of adverse childhood experiences.
Gesehen am 28.05.2020